Osteoporosis in Elderly Men - Saoussen Miladi; Meriem Sellami; Alia Fazaa; Saloua Belhadj; Kawther Ben Abdelghani; Ahmed Laatar (Current Overview on Disease and Health Research Vol. 3, 2022)
Background: Osteoporosis (OP) in elderly men remains underdiagnosed and underappreciated. After a low trauma fracture, a man is less likely to have evaluation and treatment in spite of all complications. In the present study, we aimed to determine the frequency and specificity of OP in elderly Tunisian men, and secondarily to look for the specificity of risk factors for male OP, its complications, and management. Methods: This is a retrospective study of the records of male patients over the age of 65 who were attending our rheumatology department during a period of 14 years. All patients underwent bone mineral density (BMD) measurement with an assessment of bone mass at the femoral and vertebral sites. Results: Fifty-nine patients were included with an average age of 71 years. Twenty-seven patients (46%) had OP and 19 (32%) had osteopenia. The average age of osteoporotic patients was 72.2 years. Fifty-four percent of our patients were smokers, of whom 88% had bone loss. Three patients (3%) with a low body mass index (<19kg /m2) were osteoporotic. OP was secondary to a known potentially OP-induced pathology in 28 patients (47%). An iatrogenic origin of OP was found in 21 patients (36%), mainly by corticosteroids. Thirty-nine bone low energy fractures were noted, including 25 (64%) vertebral fractures and 8 (20%) upper femur fractures. Twenty-one fractures (54%), including 16 vertebral fractures, were associated with OP. Only one death was lamented following a fracture of the upper end of the femur. All our osteoporotic patients and 17 patients (90%) of osteopenic patients had vitamin D and calcium supplementation. Twenty-seven (46%) patients had received bisphosphonate treatment without reporting adverse events. Conclusion: As in all published studies, OP was mostly secondary among older men, but much more common. Low energy fractures were also common at the vertebral site.